1000 amazing weird facts - Mills, Andrea; Harris, Michelle; Hoffman, Steven M; Lamichhane, Priyanka (London dorling kindersley limited, 2023)
This weird and wonderful fact book for children will teach them about all kinds of bizarre beasts, incredible places and peculiar phenomena. Did you know there's a plant that eats mice? Or that you can dip your toe in a rainbow-colored river? Whether it's geography, people, places, animals, plants, or weather, 1,000 Amazing Weird Facts is the ideal book for curious young minds who are fascinated by our amazing planet
The world around us
Keywords: general knowledge